Echocardiographic predictors of atrial fibrillation in middle-aged patients without overt heart disease. (25th November 2020) - Borizanova-Petkova, A; Georgieva, N; Kinova, E; Goudev, A; Koleva, V
Abstract: Background: Left atrial volume index (LAVi) has been established as a surrogate marker for chronically elevated left ventricular (LV) filling pressure. Moreover it is a powerful predictor of atrial fibrillation (AF) in different pathologies. However, there is limited data for additional and sensitive echocardiographic predictors of AF in patients without over heart disease. Purpose: To investigate middle- aged AF patients without overt heart disease and to identify additional echocardiographic predictors of AF. Methods: A total of 936 consecutive patients with AF, who had been admitted for sinus rhythm restoriation in our hospital for the period January 2016- December 2018, were screened for participation in the study. Only 70 patients met the inclusion criteria- stable sinus rhythm, age between 40–60 years, without over heart disease. They were separated in 2 groups: with new onset AF (n=33) and recurrent AF (n=37); 30 healthy subjects were enrolled in the control group. All patients underwent two dimensional echocardiographic assessment with volumetric and speckle tracking analyses. Results: There were significant differences between all groups in: LAVi; LA total (LATEF), passive (LAPEF) and active (LAAEF) emptying fractions; LA reservoir (LASr), conduit (LAScd) and contractile (LASct) strain; LV global longitudinal strain (GLS), but not in other LV indices – table. Multiple regression analysis demonstrated that LAVi (B=0.012, p=0.05, 95% CI: 0.000–0.023), LASr (B=−0.055, p=0.0001, 95% CI: −0.071 to −0.039), LASct (B=0.041, p=0.001, 95% CI: 0.016–0.066) are independent predictors of AF. Conclusion: In middle- aged patients without overt heart disease LASr and LASct have additive value beyond LAVi in prediction of AF. Funding Acknowledgement: Type of funding source: None